(untitled) - Grenby, M. O. (Cambridge, 2001)
The French Revolution sparked an ideological debate that brought Britain to the brink of its own revolution in the 1790s. As radicals turned to the writing of "Jacobin" fiction, the fear of rebellion prompted conservatives to write novels. This is the first book to examine the extent and variety of Anti-Jacobin fiction. As well as identifying an unprecedented number of these novels and considering what they contain, M.O. Grenby investigates why they were written, especially by women, and why they proved to be so popular.
Keywords: English fiction,France,France,Văn học và lịch sử,Pháp,Pháp; History and criticism,History,Literature and the revolution,History,Foreign public opinion, British,Lịch sử và phê bình.,Lịch sử,Văn học và cách mạng,Dư luận nước ngoài, Anh,Lịch sử; 18th century,Revolution, 1789-1799,Revolution, 1789-1799,Thế kỷ 18,Cách mạng, 1789-1799,Cách mạng, 1789-1799